Pediatric drug regulation: International perspectives. Issue 6 (14th April 2019) - Baum, Victor C.; Bax, Ralph; Heon, Dominique; Yang, Zhimin; Sakiyama, Michiyo
Summary: There was a time when the predominant approach to exposing children to new drugs was to protect children from research. This has evolved over the past several decades into protecting children through research. To encourage pediatric studies and approval of pediatric medicines, governments have provided financial incentives as well as obligations/requirements for pharmaceutical companies to carry out pediatric studies in certain circumstances. The unique considerations for children have been acknowledged by the various governments and drug regulatory agencies through international dialogue and cooperation among patient and patient care representatives, regulatory agencies, and academic, clinical and manufacturing stakeholders. We describe pediatric drug regulation in five of the largest international drug regulatory agencies and additionally discuss efforts at international cooperation and discussion in pediatric drug regulation.